Microbial population dynamics in a semi-continuous anaerobic system treating lipid-rich wastewater - Nguyen, Kiem Khac; Ballesteros, Florencio C. Jr. (Quezon City College of Engineering, University of the Philippines Diliman, 2017)
Lipid-rich wastewaters are an ever-growing environmental concern. These wastewaters, which can be traditionally characterized as fats, oils, and greases (FOG), come from domestic sewage and industrial effluents of restaurants and food services, food processing facilities, vegetable oil plants, dairy industries, livestock farms, wool scouring facilities. FOG reduce operational performance and they are the main reasons of process failure in traditional anaerobically biological wastewater treatment plants because of flotation, waste discharges, unpleasant odors, blockages, and inhibiting the contact between soluble substrates and biomass. The main objective of this work is to find out the microbial groups responsible for the anaerobic digestion of lipid-rich wastewaters. To accomplish the main objective, first we characterized sludge and substrate properties; then we revealed microbial groups responsible for each step of oil anaerobic degradation; finally, we investigated how the key oil degraders change when disturbance applied. The results from our first research revealed that granular sludge became active and was able to produce a stable amount of methane after two weeks of acclimation to GAL. Moreover, anaerobic digestion of GAL was inhibited by LCFA at the concentration of 1 g L' LCFA. The anaerobic digestion of glycerol, LCFA and soybean oil was able to accomplish using one-month-old acclimated sludge. For LCFA and oil, although they were ready for anaerobic digestion, lag phases were much longer than glycerol. The outcomes from this research are helpful for understanding anaerobic digestion of lipid-rich wastewater, and especially guideline for experimental design in next research In the second research, semi-continuously fed reactors with three related substrates glycerol, long-chain fatty acids (LCFA) and oil, and stepwise increase in organic loading rate (OLR) were conducted for 90 days. Microbial community was analyzed using Next Generation Sequencing (NGS) with Miseq Illumina platform. By comparing changes in microbial community in three types of operations we found that Clostridiales, Bacteroidales, and Spirochaetales orders were important for glycerol degradation while Syntrophobacterales and Thermobaculales orders including Leptospirales were shown to have played a crucial role in the B-oxidation step of LCFA mineralization. This is a significant finding as the participation of Leptospirales has not been reported in the literature. The results also suggest that feeding single related substrate while gradually increasing OLR and using NGS provides a clearer picture of the population dynamics occurring at given conditions. In the final research, an artificial disturbance designed by a ten days' period of starvation was applied to anaerobic systems to evaluate the stability of microbial groups involved in degradation of soybean oil and its components. The dynamics of microbial community was traced by NGS, compared to before the disturbing event and linked to reactor performance. The results showed that the microbial community was shifted profoundly, leading to declining methane production after 40 days of re-feed in reactors treated LCFA and soybean oil. The abundance of orders Clostridiales, Spirochaetales and Desulfovibrionales was essential to overcome the difficult period in the reactors fed with glycerol. More interestingly, a strong correlation was found between LCFA degrading orders, namely Thermobaculales, Syntrophobacterales, and Leptospirales performance of reactors fed with LCFA and soybean oil. The results also revealed that orders Actinomycetales, Synergistales, and Thermotogales as background organisms which did not contribute to glycerol, LCFA nor oil degradation, were able to surpass other useful bacteria and increased their relative abundance when methane production was ceased.
Thesis (Ph.D. Environmental Engineering)--University of the Philippines Diliman
Keywords: Sewage -- Purification -- Anaerobic treatment